FERTILIZERS ON PRODUCTION OF OLIVE ROOTED STEM CUTTINGS ‘ARBEQUINA’ - VIEIRA NETO, João; CANÇADO, Geraldo Magela de Almeida; OLIVIERA, Adelson Francisco de; MESQUITA, Hugo Adelande de; LÚCIO, Alessandro Dal’col; SILVA, Luiz Fernando de Oliveira da (Scientia Agraria, 2010)
In this work evaluated the effect of fertilizers in the final phase of olive rooted stem cuttings production. The experimental set was carried out in the Experimental Farm of EPAMIG, located in the city of Maria da Fé, Minas Gerais State, Brazil. The work developed with rooted hard-cuttings of Arbequina cultivar started in beginning of February 2008. The experimental design was of completely randomized plots with four replicates of 12 plants for each experimental plot. The plants were cultivated in pots containing 2 dm3 of soil substratum. Four commercial fertilizers were evaluated: Ativo®; Brotax-Micro®; Fert Bokashi®; and Nippoterra®, in five concentration levels (cm3 dm-3): 0; 1; 2; 3; and 4. All fertilizer treatments were applied at 15-days intervals during the period of 120 days and each experimental plot was sprayed with 0,5 dm3 of treatment solution. After 60 days the average number of buds and bud length were evaluated. Further, after 120 days of treatment, were evaluated the averages of shoot and root length; root number; shoot fresh and dry weight; and root fresh and dry weight. During the last phase of olive rooted cuttings production, the treatments using the fertilizers Ativo®, Brotax-Micro®, Fert Bokashi® and Nippoterra® showed better result than the treatment control (no fertilizer). The fertilizers with the best performance were Brotax-Micro® and Nippoterra® while the dosage of 4 cm3 dm-3 showed the higher response for all fertilizers tested.